(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article describes the large-scale reforms aimed at creating favorable conditions for doing business in tax and finance, improving the investment environment, and further strengthening the confidence of business circles in our republic in recent years. At the same time, such areas as underground trade and general catering, transport by motor vehicle, housing construction and repair, provision of residential services are studied, foreign experience and scientific-practical conclusion on its application in our country are studied. and suggestions are formulated.